Training on Converting Theses to Articles and Adapting Journal Templets for Unima Sociology Education Students - Mesra, Romi; Lasut, Meiske; Apada, Magfira Satya; Ngumarno, Jayus; Tuerah, Paulus Robert; Tuerah, Roos Marie Stella; Sufitriyono, Sufitriyono (Abdi Masyarakat, 2023)
Training of Conversion thesis to article is expected to make it easier for future students to complete a comprehensive test requirement where one of the conditions is to create an article based on a revised essay that will be published in a reputable journal. It is also to avoid students paying others to make the article so that students can make it independently. The aim of this service is to conduct training on Converting Theses to Articles and Adapting Journal Templates for Unima Sociology Education Students so that students can master these skills. The methods used in this activity include lectures, discussions, questions and answers and of course direct practice. After carrying out the training, it can be that several steps in implementing this training are as follows: 1. Make sure the thesis file plagiarism is low below 30%, 2. Open the thesis word file, 3. Open the published journal/journal article word template file, 4. First adjust the title, author, affiliation and email address, 5. Create an abstract in English and Indonesian, consisting of: a. Background/Aim, b. Research methods, c. Method of collecting data, d. Data analysis, e. Research result, 6. Copy and paste the following from the thesis into the article: a. Introduction, b. Methods (research methods, data collection techniques/methods, c. Data analysis), d. Results (Interviews, observations, documents) and Discussion (Following results/findings, theories, references, researchers' opinions), e. Conclusion, f. Bibliography